Evaluasi Manajemen Risiko Teknologi Informasi Menggunakan Framework COBIT 5 (Studi Kasus : PT. Kimia Farma (Persero) Tbk - Plant Watudakon) - Novia Dwi Setyaningrum; Suprapto Suprapto; Ari Kusyanti (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Information technology is almost implemented in all companies, including the PT.Kimia Farma plant Watudakon this company has implemented information systems based on Enterprise Resource Planning (ERP). Using information systems certainly has many risk opportunities. In the event of a problem will have an overall impact. As is often the case, the system issues on the part of the warehouse, then the process of receiving data information from the warehouse for finance will be disrupted, which may occur due to server down or other problems. Therefore, risk management is required to manage all possible risks. So this research was conducted to determine the value of capability level by evaluating the risk management PT.Kimia Farma using COBIT 5 framework on domain EDM03 (Ensure Risk Optimization) and APO12 (Managed Risk). The data were collected by questionnaire, observation and interview. From the data, we get the capability level for EDM03 at level 2 and APO12 at level 1. After knowing the level of risk the next step is to conduct a risk assessment to determine risks that are still within the company's risk appetitte, then to determine risk mitigation measures. From the results of the two analyzes will be a reference as the preparation of recommendations. Proposed recommendations such as the preparation of risk profile documents, establishing management to manage risk.